2012
DOI: 10.1186/1756-9966-31-26
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin induces growth of metastatic tumors in a preclinical model of non-small lung cancer

Abstract: Osteopontin (OPN), also known as SPP1 (secreted phosphoprotein), is an integrin binding glyco-phosphoprotein produced by a variety of tissues. In cancer patients expression of OPN has been associated with poor prognosis in several tumor types including breast, lung, and colorectal cancers. Despite wide expression in tumor cells and stroma, there is limited evidence supporting role of OPN in tumor progression and metastasis. Using phage display technology we identified a high affinity anti-OPN monoclonal antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 54 publications
5
37
0
1
Order By: Relevance
“…Thus rather than inducing migration by inducing acquisition of a mesenchymal state [9], or by binding to phosphatidylserine at the cell surface, as described for intestinal epithelial cells [22], MFGE8 here is instead a chemoattractant for tumor cells. How this function is regulated, and whether the receptors involved are also αvβ3/5 integrins will have to be evaluated, but it seems similar to a recently described effect of another ligand of αvβ3/5 integrins, osteopontin, on lung cancer [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus rather than inducing migration by inducing acquisition of a mesenchymal state [9], or by binding to phosphatidylserine at the cell surface, as described for intestinal epithelial cells [22], MFGE8 here is instead a chemoattractant for tumor cells. How this function is regulated, and whether the receptors involved are also αvβ3/5 integrins will have to be evaluated, but it seems similar to a recently described effect of another ligand of αvβ3/5 integrins, osteopontin, on lung cancer [23]. …”
Section: Discussionmentioning
confidence: 99%
“…In each of the studies, abrogating the expression of OPN resulted in decreased proliferation and/or survival, malignant and/or metastatic potential. In NSCLC, the use of a monoclonal antibody AOM1 identified using phage display technology was shown to be effective in significantly inhibiting growth of large metastatic tumors in the lung when used as a single agent or in combination with Carboplatin (Shojaei et al, 2012). …”
Section: Approaches To Inhibit Opn Expression And/or Functionmentioning
confidence: 99%
“…Evidence for the involvement of SPP1 in human malignancies indicates SPP1 as one of the promotors in multiple cancers. For instance, in colon cancer, SPP1 is highly expressed and significantly promotes tumor cell proliferation and angiogenesis (24); in non-small lung cancer, high expression of SPP1 induces tumor growth and enhances cell mobility (25). Recently, several studies have observed and suggested SPP1 as an indicator of the prognosis in GC (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%